Souvenir Sales Analysis using Apriori Algorithm (Case Study: Ubud-Market Transaction in March 2020) - Rizky, Muhammad Firyanul; Arya Kadyanan, I Gusti Agung Gede; Made Mahendra, Ida Bagus (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021DO - 10.24843/JLK.2021.v10.i01.p10, 2021)
Ubud market is one of the largest art markets in Bali, there are many local Balinese souvenir traders and craftspeople, most of them are livelihoods depend on buying and selling local souvenirs ,  Since the Covid-19 pandemic entered in April 2020, Ubud market traders have started to close their business and hoping economic recoveryin future. The author tries to do a track record of souvenir sales transactions in Ubud market to find the last sales pattern before the traders closes their business to give a solution for marketing strategies in future .  T he sales transaction data will just become meaningless trash  if it’s useless ..   To get  use  information about the products that are most sold  out  at Ubud Market from  the  transaction database, the author uses the Apriori algorithm.   This study was determined final rules on 2 itemset combination, If buying Manik-Manik Craft, Also buy Barong Shirt with the highest confidence 70% and Minimum Support 28%, and for 3 itemset a combination, If buying Celuk Silver, and Barong Shirt, Also buy Manik-Manik Craft with the highest confidence 37.5% and Minimum Support 12%, based on that there are 3 best-selling souvenir products, namely Barong Shirt, Manik-Manik Craft and Silver-Celuk in March 2020. Keywords :  Apriori Algorithm, Data Mining, Sales Analysis, Association Rule Mining, Ubud Market.